Emerging Threats to Food Security among Rural Households in the Kassena-Nankana Municipality - Apwah, Frederick (2015)
A Thesis submitted to the School of Graduate Studies Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment of the requirements for the degree of Master of Science in Development Policy and Planning.